High energy electron radiation inducing non-homogeneous structural changes on single layer graphene/SiO2/Si substrate - Guzali, Hazim; Ayob, Nur Idayu; Mohamad, Muhammad Naim Hanif; Zamzuri, Ahmad Syahmi; Che Hak, Cik Rohaida; Ahmad, Zuraida; Md Ralib @ Md Raghib, Aliza 'Aini (Elsevier, 2025)
Graphene’s performance under radiation is crucial for its potential applications in radiation-hardened electronics. In this study, we investigate the physical topology and lattice modification of single layer graphene (SLG) grown on a SiO2/Si substrate when exposed to high energy (MeV) electron radiation. SLG samples, synthesized via chemical vapor deposition (CVD), were irradiated with a 3 MeV electron beam at doses of 50 kGy, 100 kGy, and 200 kGy. Raman microscopy and Field Effect Scanning Electron Microscopy (FESEM) were employed before and after radiation to analyze the microstructural and lattice changes. Our findings reveal that at 200 kGy, certain regions of the sample exhibit G band splitting in the Raman spectra, correlating with FESEM images showing wrinkles, ripples, and folded-like structures. This suggests interactions between surface charges and graphene phonons due to high-energy electron radiation, along with strain-induced lattice distortions in disordered graphene. Interestingly, other regions maintain the sharp shape of G and 2D bands, with a smaller D band peak, indicating minimal structural disorder. The weak defect peak suggests the early stages of amorphization caused by radiation-induced defects. These results highlight the non-homogeneous structural changes in SLG under high energy electron radiation, emphasizing the complex effects of radiation on graphene.